Diagnostic study of a high‐precipitation event in the Western Mediterranean: adequacy of current operational networks. (25th August 2015) - Khodayar, S.; Raff, F.; Kalthoff, N.; Bock, O.
Abstract : To investigate whether the spatial and temporal resolution of current operational observing systems in the Western Mediterranean (WMed) region suffice to adequately represent the atmospheric processes responsible for the initiation and intensification of convection, a diagnostic study of the HyMex Intensive Observation Period 8 (IOP8) is performed. During the IOP8, heavy rainfall with intense lightning and consequent devastating flash floods occurred in the WMed region. The synergy of operational networks in the northern WMed, including Global Positioning System (GPS) stations, rain gauges, weather stations, lightning sensors and radiosondes, was used to document in detail the evolution of the heavy precipitation event. In general, the resolution of the aforementioned networks adequately sampled the temporal and spatial variability of the atmospheric water vapour, as well as the position of mesoscale convergence zones which played a key role in the initiation and evolution of convective systems in this case. Nevertheless, high uncertainty was associated with the existence and location of moisture convergence zones and wind convergence lines over the sea, reflecting the need for model analysis and remote‐sensing observations to complete the documentation of the event.